Chemical Functionalization Effects on Cubane-Based Chain Electronic Transport. (9th August 2015) - Katin, Konstantin P.; Maslov, Mikhail M.
Abstract : We report electronic structure calculations in chemically functionalized linear cubane-based chains. The effects of covalent chemical attachments on chain transport properties are examined with nonorthogonal tight-binding model (NTBM) considering Landauer-Büttiker formalism. The covalent bonding of even a single-type functional group is shown to considerably alter the conductance of the chain. For similar radical doping density, electronic characteristics are found to range from insulator to narrow-gap semiconductor depending on the nature of the covalent bonding. Therefore it has become possible to tune electronic properties of the cubane-based one-dimensional oligomers by the functionalization for nanoelectronic applications.